The Bi2Se3–Bi2Te3–BiI3 system: Synthesis and characterization of the BiTe1-xSexI solid solutions. (September 2019) - Aliev, Ziya S.; Ahmadov, Elvin C.; Babanly, Dunya M.; Amiraslanov, Imamaddin R.; Babanly, Mahammad B.
Abstract: This paper describes the phase relationships and ternary solubility of the binary and ternary compounds in the Bi2 Se3 –Bi2 Te3 –BiI3 system. Differential thermal analysis (DTA), powder X-ray diffraction (PXRD) and scanning electron microscope equipped with energy dispersive X-ray spectrometer (SEM-EDS) were main tools for experimental investigations of the equilibrated samples of the system. This system is found to be quasi-ternary plane of the quaternary Bi–Se–Te–I system. An isothermal section at 300 K, a liquidus surface projection and four isopleth sections of the system were plotted based on experimental and literature data. The existence of the BiTe1-x Sex I solid solutions series (γ1 and γ2 ) in the wide range of composition of BiSeI–BiTeI section was revealed and characterized. No new quaternary compound was found in the system. The primary crystallization fields and homogeneity range of all the existing phases, as well as character and temperature of all the non- and monovariant equilibria of the system were determined. Highlights: The phase diagram of the Bi2 Se3 -Bi2 Te3 -BiI3 quasi-ternary system is constructed. The existence of the wide solid solubility fields was revealed. The crystal lattice parameters and homogeneity areas for the BiSex Te1-x I solid solutions were determined.